2014
DOI: 10.1155/2014/563160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet on Brain Plasticity in Animal and Human Studies: Mind the Gap

Abstract: Dietary interventions have emerged as effective environmental inducers of brain plasticity. Among these dietary interventions, we here highlight the impact of caloric restriction (CR: a consistent reduction of total daily food intake), intermittent fasting (IF, every-other-day feeding), and diet supplementation with polyphenols and polyunsaturated fatty acids (PUFAs) on markers of brain plasticity in animal studies. Moreover, we also discuss epidemiological and intervention studies reporting the effects of CR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 256 publications
(369 reference statements)
3
143
0
4
Order By: Relevance
“…Additionally, food restriction has recently been suggested to affect learning and performance in memory and discrimination tasks (Makowiecki et al 2012;Kuhla et al 2013;Talhati et al 2014). On a more general level, direct effects of food restriction on brain plasticity have been reported (Murphy et al 2014). Caloric restriction leads to changes in synapse number and structure (Mattson 2012), increased NMDA receptor expression (Yilmaz et al 2011), and up-regulation of BDNF (Mattson and Wan 2005;Kishi and Sunagawa 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, food restriction has recently been suggested to affect learning and performance in memory and discrimination tasks (Makowiecki et al 2012;Kuhla et al 2013;Talhati et al 2014). On a more general level, direct effects of food restriction on brain plasticity have been reported (Murphy et al 2014). Caloric restriction leads to changes in synapse number and structure (Mattson 2012), increased NMDA receptor expression (Yilmaz et al 2011), and up-regulation of BDNF (Mattson and Wan 2005;Kishi and Sunagawa 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In light of its crucial roles in pre-and postnatal development of the brain, particularly during the critical windows of rapid brain growth, differentiation and lipid accumulation, interest has grown for gangliosides as a dietary component [3]. Exogenous administration of sialic acid, either bound or free, in animal model studies, has been shown to increase sialic acid concentrations in gangliosides and glycoproteins of the animal brain leading to improved learning [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Calorie restriction, intermittent fasting and dietary content and their effects on neural plasticity, including AHN, in animal and human studies have been reviewed [6], with it concluded that these dietary factors have been demonstrated to promote neural plasticity. However, the mechanisms underlying these perceived effects remain to be elucidated, but in the meantime, placing importance on dietary content, frequency and amount could be a cost-effective way of preventing and ameliorating cognitive decline and mood disorders [6,24]. Conversely, negative regulators of AHN include stress, chronic sleep deprivation, ageing, inflammation and depression [25][26][27][28].…”
Section: Modulation Of Ahnmentioning
confidence: 99%
“…Several environmental stimuli are in fact thought to enhance AHN, such as physical exercise and diet [6,7]. Interestingly, not only diet content can modulate AHN, but also meal frequency, calorie intake and texture [8].…”
Section: Introductionmentioning
confidence: 99%